Primer registro documentado de Salteador Grande (Stercorarius pomarinus) en Argentina continental - Rodriguez Astorino, Lautaro Nicolás; Rodriguez Astorino, Sol Valentina; Rodriguez Astorino, Tomás Nazareno; Rodriguez, Claudio (Nuestras Aves, 2013)
Este artículo no cuenta con un resumen.